Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Carbon footprint assessment of Taiwan's aquaculture industry integrated with solar photovoltaics: A comprehensive review - Hsin-Yi Liu; Asif Ali Bhat; Yu-Wei Chen; Shin-Yu Chen; Ming-Kuei Shih; Kuo-Huan Ting; Chia-Hua Lin; Chih-Yao Hou (Aquaculture, 2026)

Opposite latitudinal biodiversity gradient in the open ocean generated by transition zones: Insights from fish distribution in the Northwest Pacific - Yuan Lin; Zeshu Yu; Sk Istiaque Ahmed; Xueding Wang; Tomihiko Higuchi; Itsuka Yabe; Marty Kwok-Shing Wong; Sachihiko Itoh; Eisuke Tsutsumi; Hiroaki Saito; Kosei Komatsu; Atsushi Tsuda; et al. (Progress in Oceanography, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Patterns in marine surface fish biodiversity and community composition detected by different eDNA metabarcoding sampling methods - Sk Istiaque Ahmed; Zeshu Yu; Tomihiko Higuchi; Jun Inoue; Marty Kwok-Shing Wong; Xueding Wang; Yuan Lin; Sachihiko Itoh; Kosei Komatsu; Eisuke Tsutsumi; Hideki Fukuda; Susumu Hyodo; et al. (Journal of Oceanography, 2026)
Understanding marine surface fish diversity is crucial for ecosystem management. However, the traditional sampling methods are often invasive, costly, or unsuitable for certain species or locations. Environmental DNA (eDNA) metabarcoding provides a non-invasive and relatively cheap alternative to explore patterns of diversity. It is important to recognize that, eDNA-based inference can vary across sampling methods, potentially impacting the validity of biodiversity assessments. To evaluate and compare the effectiveness of three eDNA sampling methods—ship-bottom intake (4.5 m), Niskin bottles (5 or 10 m), and bucket (0 m)—for assessing fish diversity and fish community composition in the western North Pacific near Japan, we analyzed fish communities from 83 stations sampled during nine research cruises. Taxonomic analysis revealed that each method detected over 324 taxa, contributing to a total of 465 taxa. Hierarchical clustering generally identified similar species composition across methods at a station. The exception was when intake samples, collected at different times, diverged from bucket and Niskin samples at the same station. Hill’s number rarefaction and extrapolation curves across all clusters showed similar results among methods, with exceptions in a few clusters where bucket samples exhibited higher biodiversity indices than intake and Niskin samples. Non-metric multidimensional scaling indicated significant relationships between cluster composition and environmental factors like temperature, salinity, and chlorophyll-a. Some clusters were also controlled by integrated seasonal factors. Overall, fish community composition was convincingly similar among methods. This finding suggests that any of these eDNA sampling methods can be effective and may be prioritized based on logistical considerations.

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Environmental DNA of small pelagic fish in the deep ocean - Zeshu Yu; Marty Kwok-Shing Wong; Jun Inoue; Yuan Lin; Itsuka Yabe; Tomihiko Higuchi; Susumu Hyodo; Sachihiko Itoh; Yuichiro Nishibe; Hajime Obata; Shin-ichi Ito (Progress in Oceanography, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Fish species detection by environmental DNA metabarcoding by three surface sampling methods - Sk Istiaque Ahmed; Zeshu Yu; Tomihiko Higuchi; Jun Inoue; Marty Kwok-Shing Wong; Susumu Yoshizawa; Sachihiko Itoh; Kosei Komatsu; Yusuke Kawaguchi; Eisuke Tsutsumi; Yuan Lin; Susumu Hyodo; et al. (Regional Studies in Marine Science, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

How does globally accumulated tropical cyclone energy vary in response to a changing climate? - Kaiyue Shan; Fengfei Song; Yanluan Lin; Wenchao Chu; Chengfei He; Pao-Shin Chu; Lixin Wu; Xiping Yu (Science Bulletin, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

Spatiotemporal variation and inter-transport of atmospheric speciated mercury between Kaohsiung Harbor and neighboring urban areas - I-Chieh Tu; Chung-Shin Yuan; Yu-Lun Tseng; Chia-Wei Lee; Chitsan Lin (Environmental Pollution, 2024)

A numerical investigation of an indoor dry storage facility on heat transfer - Chia-Wei Lin; Yung-Shin Tseng; Kai-Qi Lin; Yu-Hsuan Chang; Tzu-Chen Hung; Hua-Yi Hsu (Annals of Nuclear Energy, 2024)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

Investigation of the fall armyworm (Spodoptera frugiperda) gut microbiome and entomopathogenic fungus-induced pathobiome - Yao-Chia Liu; Tzu-Han Chen; Yu-Feng Huang; Chang-Lin Chen; Yu-Shin Nai (Journal of Invertebrate Pathology, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

Chemical fingerprints and source resolution of atmospheric fine particles in an industrial harbor based on one-year intermittent field sampling data - Yu-Lun Tseng; Chung-Shin Yuan; Kwok-Wai Wong; Chitsan Lin (Science of The Total Environment, 2023)

Development of innovative marker detection methods for high-fertility ducks (Anas plastyrhynchos) - Hsiu-Lin Huang; Hsiao-Lung Liu; Yu-Shin Cheng (Theriogenology, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Characteristics of Old-Growth and Secondary Forests in Relation to Age and Typhoon Disturbance - Shin-Yu Lin; Pei-Jen Lee Shaner; Teng-Chiu Lin (Ecosystems, 2018)

Characterization of Eptesipoxvirus, a novel poxvirus from a microchiropteran bat - Shin-Lin Tu; Yoshinori Nakazawa; Jinxin Gao; Kimberly Wilkins; Nadia Gallardo-Romero; Yu Li; Ginny L. Emerson; Darin S. Carroll; Chris Upton (Virus Genes, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Development of Home-Based Frailty Detection Device Using Wireless Sensor Networks - Chung-Chih Lin; Chun-Chang Chen; Pay-Shin Lin; Ren-Guey Lee; Jing-Siang Huang; Tsai-Hsuan Tsai; Yu-Chuan Chang (Journal of Medical and Biological Engineering, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

In Vivo Sodium MRI for Mouse Model of Ischemic Stroke at 7 T: Preliminary Results - Kun-Che Lee; Jen-Fang Yu; Yi-Shin Lee; Guo-Jen Huang; Hsiao-Lung Chan; In-Tsang Lin; Jyh-Honrg Chen (Journal of Medical and Biological Engineering, 2015)

Photodegradation of Alachlor Using BiVO4 Photocatalyst Under Visible Light Irradiation - Yi-Kuo Chang; Yu-Shen Wu; Chung-Shin Lu; Pei-Feng Lin; Tsung-Yen Wu (Water, Air, & Soil Pollution, 2015)

A new design method for extracorporeal high-intensity focused ultrasound annular array - Gin-Shin Chen; Yu-Cheng Lin; Chu-Chiang Chen (Medical & Biological Engineering & Computing, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Variation in life-history traits for micro-cohorts of Sepioteuthis lessoniana in the waters off northern Taiwan - Chih-Shin Chen; Jing-Yu Chen; Chiao-Wen Lin (Fisheries Science, 2015)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Chemoselective synthesis, antiproliferative activities, and SAR study of 1H-pyrazol-5-yl-N,N-dimethylformamidines and pyrazolyl-2-azadienes - Kau-Shan Wen; Hui-Yi Lin; Yu-Ying Huang; Kimiyoshi Kaneko; Hiroyuki Takayama; Masayuki Kimura; Shin-Hun Juang; Fung Fuh Wong (Medicinal Chemistry Research, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Directed Mutagenesis of the Conserved Asparagine Residues of Bacillus Stearothermophilus Leucine Aminopeptidase II - Ruey-Shyang Chen; Shin-Ling Yang; Yu-Wen Hua; Meng-Chun Chi; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)